Individual and Team Sports aged (13-15) Years Old - Gaseous, Abdul Wahab (Journal of Physical Education, 2016)
The research aimed at identifying the differences in the emotional intelligence of some Individual and team sport players according to gender and age. The subject of research represented (80) male and female players. The results were collected and treated using (SPSS). The researchers concluded that all individual and team sport male and female players have close emotional intelligence degrees. Finally the researcher recommended making similar studies on emotional intelligence on other variables.